Perancangan PLTMH Kapasitas 30 kW, Desa Giritirta, Kec. Pejawaran, Banjarnegara, Jawa Tengah - Vendy Antono; Caesar Febria Awal Ramadhana Yusreza (JURNAL POWERPLANT, 2016)
Utilization of water as electrical energy is a form of exploitation of natural resources as a renewable energy that is free of smoke and fuel. Mrawu river, Giritirta located in the village, district Pejawaran, Banjarnegara, Central Java has the potential for the development of Micro Hydro Power Plant. In designing this Micro Hydro , rapid optimum diameter pipe ( penstock ) D = 0.42 m , 52 m length of pipe , and the pipe thickness t = 10 mm , the author uses Crossflow turbine , with a design quantity Q = 0.35 m3 / s , and Head H = 14.5 m . Obtained power generated by P = 30 kW . With these data Main dimensions planned this crossflow turbine that is, the outside diameter D1 = 0.25 m runner , the inside diameter D2 = 0.17 m , width arm turbine bo = 0.4 m , the number of blades Z = 22 blade and shaft diameter Dp = 50 mm.